(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
The affective filter hypothesis highlights how emotional factors such as anxiety, motivation, and self-confidence can significantly influence second language acquisition. In online English classrooms, these emotions often become more pronounced due to reduced face-to-face interaction and increased reliance on digital communication. This study explores practical strategies to lower learners’ affective filters and reduce anxiety in virtual English environments. Through the integration of interactive tools, personalized teacher feedback, and peer collaboration, learners experience more comfort, confidence, and willingness to participate.